Beyond Myths: Understanding the Efficacy and Safety of Traditional Medicinal Practices - Shahin Akhondzadeh (Case Reports in Clinical Practice)
Throughout history, every country and civilization have utilized the medical practices and pharmacological knowledge available to them at the time. This is particularly true for Iran, historically known as the Persian Empire, which has produced renowned scientists such as Abu Ali Sina (Avicenna) and Razi (Rhazes), along with numerous esteemed doctors and pharmacists [1]. The medical science and pharmacy of that era were relevant to their time, much like many medicines from just 50 years ago that have since been abandoned due to concerns about their effectiveness and side effects. While some of these historical practices are no longer applicable, they remain an important part of the history of medicine and deserve recognition [2]. However, there are instances where traditional medicine from various cultures has gained scientific acceptance through rigorous experimentation and modern methodologies. Many traditional remedies have been integrated into contemporary medical practice and are often included in scientific reference texts under the categories of “alternative medicine” or “complementary medicine.” It is a misconception to assume that all ancient practices lack merit [3]. For instance, lithium, which has been approved by the FDA for the acute treatment of mania and maintenance therapy in bipolar disorder since 1948, remains unmatched in its efficacy. As a professional with three decades of experience in ethnopharmacology, I hold two key beliefs that I have reiterated numerous times.First, one of the most common misconceptions is that medicinal plants are inherently safe and devoid of side effects [4]. This misunderstanding has led to the unsupervised use of these plants, resulting in severe complications, including irreversible liver damage and even liver failure. Second, the distinction between “modern medicine” and “traditional medicine” is largely artificial. Any aspect of traditional medicine that has been validated through research and incorporated into current medical practice is, by definition, part of modern medicine. In the past two decades, traditional medicine schools have been established in Iran with the expectation that they will focus on aspects of traditional medicine that can be effectively integrated into modern healthcare using the latest scientific methods. Additionally, the endeavor to honor and preserve the history of medicine is a source of pride for Iran.